Yoga and physical exercise – a review and comparison. (3rd May 2016) - Govindaraj, Ramajayam; Karmani, Sneha; Varambally, Shivarama; Gangadhar, B.N.
Abstract: Yoga is a multifaceted spiritual tool with enhanced health and well-being as one of its positive effects. The components of yoga which are very commonly applied for health benefits are asanas (physical postures), pranayama (regulated breathing) and meditation. In the context of asanas, yoga resembles more of a physical exercise, which may lead to the perception that yoga is another kind of physical exercise. This article aims at exploring the commonalities and differences between yoga and physical exercise in terms of concepts, possible mechanisms and effectiveness for health benefits. A narrative review is undertaken based on traditional and contemporary literature for yoga, along with scientific articles available on yoga and exercise including head-to-head comparative trials with healthy volunteers and patients with various disease conditions. Physical exercises and the physical components of yoga practices have several similarities, but also important differences. Evidence suggests that yoga interventions appear to be equal and/or superior to exercise in most outcome measures. Emphasis on breath regulation, mindfulness during practice, and importance given to maintenance of postures are some of the elements which differentiate yoga practices from physical exercises.